Efficacy of a vectorized vaccine for the control of Newcastle Disease applied in chicks in the hatchery - Sialer G., Mercedes (2020)
The present study evaluated the efficacy of a vectorized vaccine against Newcastle disease virus (vENC) applied in the hatchery. Two hundred one-day-old chicks were distributed in four experimental vaccination groups against vENC: T1: Live attenuated vaccine + inactivated vaccine, T2: Live attenuated vaccine, T3: Live attenuated vaccine + vectorized vaccine, T4: Unvaccinated control group. All chicks were also vaccinated against infectious bronchitis, Marek and Gumboro viruses at day 1. The birds were challenged on the day 26 with a highly pathogenic field pathogenic strain. Mortality, post-challenge clinical signs, necropsy lesions and antibody response against vENC were evaluated. Chicks vaccinated with the vENC vectorized vaccine had a lower mortality (2%) compared to birds vaccinated with live attenuated strains (12.5% ​​for T1 and 18.4% for T2 respectively; p<0.05). Likewise, a lower percentage of post-challenge clinical manifestations (p<0.05) and of lesions in organs at necropsy. The results indicate a better protective effect using the vectorized vaccine and its potential use for the control of vENC under field conditions.